Microwave-assisted facile synthesis of a new tri-block chitosan conjugate with improved mucoadhesion. (5th October 2015) - Badhe, Ravindra V.; Nanda, Rabindra K.; Chejara, Dharmesh R.; Choonara, Yahya E.; Kumar, Pradeep; du Toit, Lisa C.; Pillay, Viness
Highlights: Synthesis of a new microwave-assisted O -PEGylated chitosan- N -cysteine conjugate. The conjugate demonstrated a more than twice improvement in mucoadhesion compared with native chitosan. The microwave-assisted synthesis approach is a superior time and energy conserving process. The conjugate displayed reduced swelling and improved biodegradation. Abstract: A new chitosan-based tri-block conjugate, O -PEG-chitosan- N -cysteine was synthesized using microwave irradiation. For synthesis of this derivative, chitosan was modified to a PEG-chitosan conjugate followed by PEG-chitosan-cysteine using 6- O PEGylation and 2- N -thiolation, respectively. The synthesized derivative was characterized using various analytical techniques such as FT-IR and 1 H NMR spectroscopy. The conjugate was also analyzed for its biochemical, biodegradation and mucoadhesive properties. The modified chitosan conjugate exhibited improved mucoadhesion behavior (14.0 h) with greater biodegradation compared to the parent polymer (6.3 h). The in silico modeling corroborated with the in vitro study demonstrating a stable complex between mucin and O -PEG-chitosan- N -cysteine conjugate (Δ E = −60.100 kcal/mol) compared to mucin and chitosan conjugate. The synthesis proposed herein, involves the use of microwave irradiation which causes a substantial reduction in the reaction time (approximately 2.30 h) compared to conventional method (35 h).